2015
DOI: 10.1007/s40279-015-0323-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Antioxidants on Sport Performance: A Review

Abstract: Many athletes supplement with antioxidants in the belief this will reduce muscle damage, immune dysfunction and fatigue, and will thus improve performance, while some evidence suggests it impairs training adaptations. Here we review the effect of a range of dietary antioxidants and their effects on sport performance, including vitamin E, quercetin, resveratrol, beetroot juice, other food-derived polyphenols, spirulina and N-acetylcysteine (NAC). Older studies suggest vitamin E improves performance at altitude,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 103 publications
3
148
2
3
Order By: Relevance
“…Additionally, an increased exercise-induced oxidative stress is observed in individual taking high-doses of α-tocopherol (Margaritis and Rousseau, 2008). In short term, N-acetyl-cysteine (NAC; antioxidant) and allopurinol (an inhibitor of XO) do attenuate muscle damage and lipid oxidation caused by acute exhaustive exercise (Gómez-Cabrera et al, 2003; Braakhuis and Hopkins, 2015). Nevertheless, long-term intakes of these antioxidants may not be beneficial (Braakhuis and Hopkins, 2015).…”
Section: Antioxidant Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an increased exercise-induced oxidative stress is observed in individual taking high-doses of α-tocopherol (Margaritis and Rousseau, 2008). In short term, N-acetyl-cysteine (NAC; antioxidant) and allopurinol (an inhibitor of XO) do attenuate muscle damage and lipid oxidation caused by acute exhaustive exercise (Gómez-Cabrera et al, 2003; Braakhuis and Hopkins, 2015). Nevertheless, long-term intakes of these antioxidants may not be beneficial (Braakhuis and Hopkins, 2015).…”
Section: Antioxidant Interventionmentioning
confidence: 99%
“…In short term, N-acetyl-cysteine (NAC; antioxidant) and allopurinol (an inhibitor of XO) do attenuate muscle damage and lipid oxidation caused by acute exhaustive exercise (Gómez-Cabrera et al, 2003; Braakhuis and Hopkins, 2015). Nevertheless, long-term intakes of these antioxidants may not be beneficial (Braakhuis and Hopkins, 2015). Gomez-Cabrera et al further suggested that 8 weeks of vitamin C supplementation prevents training-induced mitochondrial biogenesis by suppressing the expression of SOD and GPx (Gomez-Cabrera et al, 2008).…”
Section: Antioxidant Interventionmentioning
confidence: 99%
“…Many different approaches have been investigated with the most common strategy involving elevating the total level of antioxidants [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16]. This is typically accomplished through supplementation with high levels of classic antioxidants, e.g., vitamin C, E, or glutathione [17], or engineered nutraceutical blends high in a mixture of these and other compounds [18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, acute supplementation (e.g., prior to an exercise session) may exert favorable ergogenic effects (e.g., enhanced performance and delayed muscle fatigue) [62,63,64]. On the other, chronic supplementation with antioxidants, contrary to the habitual practice, is increasingly acknowledged as detrimental compromising both redox and exercise adaptations [65,66].…”
Section: The Temporal Pattern Of Antioxidant Administrationmentioning
confidence: 99%